# If the harmonic means between two positive numbers is to their Geometric means as 12:13, the numbers are in the ratio.

A. 12:13

B. $\dfrac{1}{12}:\dfrac{1}{13}$

C. 4:9

D. $\dfrac{1}{4}:\dfrac{1}{9}$

Last updated date: 19th Mar 2023

•

Total views: 304.2k

•

Views today: 4.83k

Answer

Verified

304.2k+ views

Hint: We will compare the ratio between Harmonic mean and Geometric mean by using their general equations and try to solve this question.

Complete step-by-step Solution:

We can use the below formulas to solve the question.

Harmonic mean $=\dfrac{2ab}{a+b}$

Geometric mean $=\sqrt{ab}$

It is given in the question that the harmonic mean between two positive numbers to their geometric mean is 12:13.

We have to find the ratio of the numbers.

Let us assume the two positive numbers as a, b.

Let us consider the case of harmonic mean first. The formula for the harmonic mean for two numbers a and b is given by,

Harmonic mean $=\dfrac{2ab}{a+b}$

Now, let us consider the case of geometric mean. The formula for the geometric mean of two numbers a and b is given by,

Geometric mean $=\sqrt{ab}$

So, from question, we have;

$\dfrac{\text{Harmonic mean}}{\text{Geometric mean}}=\dfrac{12}{13}$

Substituting the known formulas of harmonic mean and geometric mean in the above equation we get,

$\dfrac{\dfrac{2ab}{a+b}}{\sqrt{ab}}=\dfrac{12}{13}$

Multiplying and dividing the LHS with $\sqrt{ab}$, we get,

$\dfrac{2\sqrt{ab}}{a+b}=\dfrac{12}{13}$

Taking 2 to RHS and simplifying further, we get,

$\begin{align}

& \Rightarrow \dfrac{\sqrt{ab}}{a+b}=\dfrac{12}{2\times 13} \\

& \Rightarrow \dfrac{\sqrt{ab}}{a+b}=\dfrac{6}{13} \\

& \Rightarrow \dfrac{a+b}{\sqrt{ab}}=\dfrac{13}{6} \\

& \Rightarrow \dfrac{a}{\sqrt{ab}}+\dfrac{b}{\sqrt{ab}}=\dfrac{13}{6} \\

\end{align}$

Simplify the terms on LHS using the roots, we get,

$\Rightarrow \sqrt{\dfrac{a}{b}}+\sqrt{\dfrac{b}{a}}=\dfrac{13}{6}.............\left( 1 \right)$

Let us assume $x=\sqrt{\dfrac{a}{b}}$

Substituting $x=\sqrt{\dfrac{a}{b}}$ in equation (1), we get,

$\begin{align}

& \Rightarrow x+\dfrac{1}{x}=\dfrac{13}{6}............\left( 2 \right) \\

& \Rightarrow \dfrac{{{x}^{2}}+1}{x}=\dfrac{13}{6} \\

\end{align}$

On cross multiplying, we get,

$\begin{align}

& 6{{x}^{2}}+6=13x \\

& \Rightarrow 6{{x}^{2}}-13x+6=0 \\

\end{align}$

We have obtained a quadratic equation. We can solve the same using the middle term split method as shown below,

$\begin{align}

& \Rightarrow 6{{x}^{2}}-9x-4x+6=0 \\

& \Rightarrow 6x\left( x-\dfrac{3}{2} \right)-4\left( x-\dfrac{3}{2} \right)=0 \\

\end{align}$

Taking $\left( x-\dfrac{3}{2} \right)$ common from the above equation, we get,

$\Rightarrow \left( 6x-4 \right)\left( x-\dfrac{3}{2} \right)=0$

Hence, we have either, $6x-4=0\ \ or\ \ x-\dfrac{3}{2}=0$

$\begin{align}

& \Rightarrow x=\dfrac{4}{6}\ or\ x=\dfrac{3}{2} \\

& \Rightarrow x=\dfrac{2}{3}\ or\ x=\dfrac{3}{2} \\

\end{align}$

So, $x=\dfrac{3}{2}\ or\ x=\dfrac{2}{3}$

Since we had assumed $x=\sqrt{\dfrac{a}{b}}$. We can now find the ratio of numbers.

Therefore, we have $x=\sqrt{\dfrac{a}{b}}=\dfrac{3}{2}\ \ or\ \ x=\sqrt{\dfrac{a}{b}}=\dfrac{2}{3}\ $

We can take the square and write,

$\begin{align}

& {{x}^{2}}=\dfrac{a}{b}=\dfrac{9}{4} \\

& or \\

& {{x}^{2}}=\dfrac{a}{b}=\dfrac{4}{9} \\

\end{align}$

So, the ratio can be $\dfrac{9}{4}\ \ or\ \ \dfrac{4}{9}$.

Now, in option only $\dfrac{4}{9}$ is given. So, we will consider $\dfrac{4}{9}$ as the correct answer.

Therefore, option (C) 4:9 is the correct option.

Note: There is an alternate method to solve this question. It is shown as below,

Given,

$\begin{align}

& \dfrac{HM}{GM}=\dfrac{12}{13} \\

& \Rightarrow \dfrac{\dfrac{2ab}{a+b}}{\sqrt{a.b}}=\dfrac{12}{13} \\

\end{align}$

Squaring and simplifying both sides, we get,

$\begin{align}

& \Rightarrow \dfrac{ab}{{{\left( a+b \right)}^{2}}}=\dfrac{36}{169} \\

& \Rightarrow \dfrac{ab}{{{a}^{2}}+{{b}^{2}}+2ab}=\dfrac{36}{169} \\

& \Rightarrow 169ab=36{{a}^{2}}+36{{b}^{2}}+72ab \\

& \Rightarrow 36{{a}^{2}}+36{{b}^{2}}-97ab=0 \\

& \Rightarrow 36{{a}^{2}}-16ab-81ab+36{{b}^{2}}=0 \\

& \Rightarrow \left( 9a-4b \right)\left( 4a+9b \right)=0 \\

\end{align}$

Taking positive value,

$\begin{align}

& \Rightarrow \left( 9a-4b \right)=0 \\

& \Rightarrow 9a=4b \\

& \Rightarrow \dfrac{a}{b}=\dfrac{4}{9} \\

& \Rightarrow a:b=4:9 \\

\end{align}$

Complete step-by-step Solution:

We can use the below formulas to solve the question.

Harmonic mean $=\dfrac{2ab}{a+b}$

Geometric mean $=\sqrt{ab}$

It is given in the question that the harmonic mean between two positive numbers to their geometric mean is 12:13.

We have to find the ratio of the numbers.

Let us assume the two positive numbers as a, b.

Let us consider the case of harmonic mean first. The formula for the harmonic mean for two numbers a and b is given by,

Harmonic mean $=\dfrac{2ab}{a+b}$

Now, let us consider the case of geometric mean. The formula for the geometric mean of two numbers a and b is given by,

Geometric mean $=\sqrt{ab}$

So, from question, we have;

$\dfrac{\text{Harmonic mean}}{\text{Geometric mean}}=\dfrac{12}{13}$

Substituting the known formulas of harmonic mean and geometric mean in the above equation we get,

$\dfrac{\dfrac{2ab}{a+b}}{\sqrt{ab}}=\dfrac{12}{13}$

Multiplying and dividing the LHS with $\sqrt{ab}$, we get,

$\dfrac{2\sqrt{ab}}{a+b}=\dfrac{12}{13}$

Taking 2 to RHS and simplifying further, we get,

$\begin{align}

& \Rightarrow \dfrac{\sqrt{ab}}{a+b}=\dfrac{12}{2\times 13} \\

& \Rightarrow \dfrac{\sqrt{ab}}{a+b}=\dfrac{6}{13} \\

& \Rightarrow \dfrac{a+b}{\sqrt{ab}}=\dfrac{13}{6} \\

& \Rightarrow \dfrac{a}{\sqrt{ab}}+\dfrac{b}{\sqrt{ab}}=\dfrac{13}{6} \\

\end{align}$

Simplify the terms on LHS using the roots, we get,

$\Rightarrow \sqrt{\dfrac{a}{b}}+\sqrt{\dfrac{b}{a}}=\dfrac{13}{6}.............\left( 1 \right)$

Let us assume $x=\sqrt{\dfrac{a}{b}}$

Substituting $x=\sqrt{\dfrac{a}{b}}$ in equation (1), we get,

$\begin{align}

& \Rightarrow x+\dfrac{1}{x}=\dfrac{13}{6}............\left( 2 \right) \\

& \Rightarrow \dfrac{{{x}^{2}}+1}{x}=\dfrac{13}{6} \\

\end{align}$

On cross multiplying, we get,

$\begin{align}

& 6{{x}^{2}}+6=13x \\

& \Rightarrow 6{{x}^{2}}-13x+6=0 \\

\end{align}$

We have obtained a quadratic equation. We can solve the same using the middle term split method as shown below,

$\begin{align}

& \Rightarrow 6{{x}^{2}}-9x-4x+6=0 \\

& \Rightarrow 6x\left( x-\dfrac{3}{2} \right)-4\left( x-\dfrac{3}{2} \right)=0 \\

\end{align}$

Taking $\left( x-\dfrac{3}{2} \right)$ common from the above equation, we get,

$\Rightarrow \left( 6x-4 \right)\left( x-\dfrac{3}{2} \right)=0$

Hence, we have either, $6x-4=0\ \ or\ \ x-\dfrac{3}{2}=0$

$\begin{align}

& \Rightarrow x=\dfrac{4}{6}\ or\ x=\dfrac{3}{2} \\

& \Rightarrow x=\dfrac{2}{3}\ or\ x=\dfrac{3}{2} \\

\end{align}$

So, $x=\dfrac{3}{2}\ or\ x=\dfrac{2}{3}$

Since we had assumed $x=\sqrt{\dfrac{a}{b}}$. We can now find the ratio of numbers.

Therefore, we have $x=\sqrt{\dfrac{a}{b}}=\dfrac{3}{2}\ \ or\ \ x=\sqrt{\dfrac{a}{b}}=\dfrac{2}{3}\ $

We can take the square and write,

$\begin{align}

& {{x}^{2}}=\dfrac{a}{b}=\dfrac{9}{4} \\

& or \\

& {{x}^{2}}=\dfrac{a}{b}=\dfrac{4}{9} \\

\end{align}$

So, the ratio can be $\dfrac{9}{4}\ \ or\ \ \dfrac{4}{9}$.

Now, in option only $\dfrac{4}{9}$ is given. So, we will consider $\dfrac{4}{9}$ as the correct answer.

Therefore, option (C) 4:9 is the correct option.

Note: There is an alternate method to solve this question. It is shown as below,

Given,

$\begin{align}

& \dfrac{HM}{GM}=\dfrac{12}{13} \\

& \Rightarrow \dfrac{\dfrac{2ab}{a+b}}{\sqrt{a.b}}=\dfrac{12}{13} \\

\end{align}$

Squaring and simplifying both sides, we get,

$\begin{align}

& \Rightarrow \dfrac{ab}{{{\left( a+b \right)}^{2}}}=\dfrac{36}{169} \\

& \Rightarrow \dfrac{ab}{{{a}^{2}}+{{b}^{2}}+2ab}=\dfrac{36}{169} \\

& \Rightarrow 169ab=36{{a}^{2}}+36{{b}^{2}}+72ab \\

& \Rightarrow 36{{a}^{2}}+36{{b}^{2}}-97ab=0 \\

& \Rightarrow 36{{a}^{2}}-16ab-81ab+36{{b}^{2}}=0 \\

& \Rightarrow \left( 9a-4b \right)\left( 4a+9b \right)=0 \\

\end{align}$

Taking positive value,

$\begin{align}

& \Rightarrow \left( 9a-4b \right)=0 \\

& \Rightarrow 9a=4b \\

& \Rightarrow \dfrac{a}{b}=\dfrac{4}{9} \\

& \Rightarrow a:b=4:9 \\

\end{align}$

Recently Updated Pages

Calculate the entropy change involved in the conversion class 11 chemistry JEE_Main

The law formulated by Dr Nernst is A First law of thermodynamics class 11 chemistry JEE_Main

For the reaction at rm0rm0rmC and normal pressure A class 11 chemistry JEE_Main

An engine operating between rm15rm0rm0rmCand rm2rm5rm0rmC class 11 chemistry JEE_Main

For the reaction rm2Clg to rmCrmlrm2rmg the signs of class 11 chemistry JEE_Main

The enthalpy change for the transition of liquid water class 11 chemistry JEE_Main

Trending doubts

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Write the 6 fundamental rights of India and explain in detail

Write a letter to the principal requesting him to grant class 10 english CBSE

List out three methods of soil conservation

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Write a letter to the Principal of your school to plead class 10 english CBSE